MENINGKATKAN KEPUASAN BELAJAR MAHASISWA MELALUI PENGGUNAAN LMS PADA BLENDED LEARNING PERGURUAN TINGGI VOKASI PARIWISATA DI JAKARTA - Roby Darmadi; Nurti Rahayu (JURNAL KEPARIWISATAAN, 2023)
The 4.0 education era has transformed students into learning centers, and information technology is crucial. Â On the other hand, tourism vocational tertiary institutions must produce graduates with competencies that meet work demands. Without reducing the practical content in learning, the Blended Learning model is a solution for using technology to achieve this goal. This study aims to analyze the role of the Learning Management System (LMS) in blended learning on perceived technology acceptance, Self-efficacy, and student engagement in student learning satisfaction. Data were collected by surveying 314 LMS users across four Jakarta tourism vocational colleges. Having been analyzed with PLS-SEM, the findings indicate that student satisfaction in blended learning is significantly affected by student perceptions, engagement, and efficacy while using LMS. Informed by these findings, vocational tourism institutions should manage their LMS to improve the overall quality of blended learning and achieve their learning objectives in the era of education 4.0.